Ibn Ḥafsûn ou la construction d’un bandit populaire - Gabriel Martinez-Gros (Revue des Mondes Musulmans et de la Méditerranée)
The most famous dissenter of the Umayyad times in Spain, Umar ibn Hafsûn (act. 880-917) actually turned out to be described as an ‘outlaw’ in the historical works of the xixth century. Why? The path of the inquiry leads to José Antonio Conde (1768-1820) and Reinhart Dozy (1821-1881). According to Conde, Ibn Hafsun’s rebellion echoes to the Spanish popular guerrilla against Napoleon, that the French and their supporters – Conde among them – used to discredit as ‘outlaws’. According to Dozy, Ibn Hafsûn is a remote ancestor of the Andalusian outlaw character, made popular by the European writers and travellers to Spain in the first part of the xixth century. In this way, philological craftsmanship was united to literary acquaintance and so paved the way to a self-proclaimed historical truth.